Human herpesvirus 6B immediate‐early I protein contains functional HLA‐A*02, HLA‐A*03, and HLA‐B*07 class I restricted CD8+ T‐cell epitopes. Issue 12 (29th October 2014) - Iampietro, Mathieu; Morissette, Guillaume; Gravel, Annie; Dubuc, Isabelle; Rousseau, Matthieu; Hasan, Aisha; O'Reilly, Richard J.; Flamand, Louis
Abstract : Human herpesvirus 6B (HHV‐6B) is a ubiquitous pathogen with frequent reactivation observed in immunocompromised patients such as BM transplant (BMT) recipients. Adoptive immunotherapy is a promising therapeutic avenue for the treatment of opportunistic infections, including herpesviruses. While T‐cell immunotherapy can successfully control CMV and EBV reactivations in BMT recipients, such therapy is not available for HHV‐6 infections, in part due to a lack of identified protective CD8 + T‐cell epitopes. Our goal was to identify CD8 + T‐cell viral epitopes derived from the HHV‐6B immediate‐early protein I and presented by common human leukocyte Ag (HLA) class I alleles including HLA‐A*02, HLA‐A*03, and HLA‐B*07. These epitopes were functionally tested for their ability to induce CD8 + T‐cell expansion and kill HHV‐6‐infected autologous cells. Cross‐reactivity of specific HHV‐6B‐expanded T cells against HHV‐6A‐infected cells was also confirmed for a conserved epitope presented by HLA‐A*02 molecule. Our findings will help push forward the field of adoptive immunotherapy for the treatment and/or the prevention of HHV‐6 reactivation in BMT recipients.